Fisherman carrying fish for sale - Mumbai Archive Project Team (Jio Institute, 2024)
Fishermen ply their trade door-to-door with the day’s fresh catch. This practice has remained unchanged over centuries. The only noticeable change is the replacement of traditional cane baskets with plastic buckets.